Os interesses e ideologias que nortearam as políticas públicas na educação no Governo Vargas 1930-1945 : o caso do Espírito Santo - Rosa, Josineide (2008)
It analyses the guidelines that have guided public policy in education in government Vargas, who in the quest for the achievement of its political project of construction of the National State gave emphasis to the formation of a national identity and the construction of the "brazilidade". The government has undertaken a greater centralization within the Union and states, naming Speakers for these federal, aiming to legitimized the power up and carry out their guidelines at the regional level. Education, in this context, playing a strategic serving as a vehicle for propaganda of the ideals of government, of building a "new man" to a New State. In the Holy Spirit, the governor João Punaro Bley Punaro, guided measures, in line with the redevelopment which was under national regarding public policies, aimed at social issues, mainly in health, education and social assistance. The priority of government at the beginning of interventoria was the strict control of public expenditure, pay the state debts, taking stringent measures to review the collection and control of municipal finances and politics, seeking greater centralization, control and streamlining of activities stemming from state movement that was formed at the federal level of construction of the legal and institutional framework of the National State. Moreover, expanded the network of state education, especially at primary level, and undertook an educational policy aiming "to vocational training, spiritual, civic, physical and eugenic of new generations" in accordance with the assumptions recommended by the new national political structure state. However, the changes undertaken in the period, both in the national scene, as state, not sought to mobilize the masses, in contrast, the school was to function "standardize" and homogenize the culture, customs, language and ideology seek by a company civilized and orderly, through an education conformed, no space, therefore, to the diverse and pluralistic coexistence. Given that, taken up the project of nationalization of education in various regions of the country in the nuclei of foreign colonization, with the closing of several schools, creating a climate of deep hostility to foreigners and their descendants. Despite centralizantes and interventionist measures implemented by the Union in education, Vargas found barriers in completing centralization sought in education, especially in the primary, due to resistance from state governments and the current state of Commitment.